Methotrexate-loaded FeAuGd nanoparticles for synergistic magnetic-hyperthermia and chemotherapy - Kayalvizhi Samuvel Muthiah; Lenin Subramanian; Yen-Lin Chen; Udesh Dhawan; Yu-Chien Lin; Ching-Li Tseng; Ren-Jei Chung (Chemical Engineering Journal, 2026)

Prioritizing key determinants of hematite photocatalysis through structure – Property contour mapping and statistical correlation analysis - TsingHai Wang; Ching-Lung Chen; Wei-Fan Kuan; Wei-Tong Li; Ching-Yao Ke; Tzu-Han Lin; Chung-Yu Guan; Huei-Ru Fuh (Process Safety and Environmental Protection, 2026)

Anti-inflammatory constituents from Murraya paniculata var. omphalocarpa - Kun-Ching Cheng; Chia-Hung Wu; Hao-Ze Li; Tsong-Long Hwang; Ping-Chung Kuo; Tian-Shung Wu (Phytochemistry Letters, 2026)

Potential role of oocyte-intrinsic fatty acid synthesis in ovarian development of the bigfin reef squid Sepioteuthis lessoniana - Hau-Wen Li; Yung-Che Tseng; Ching-Fong Chang; Guan-Chung Wu (Frontiers in Marine Science, 2026)
In most animals, excess dietary energy is stored as lipids in specialized tissues, such as the liver in vertebrates or the hepatopancreas and fat body in invertebrates, which function as energy reservoirs for reproduction. In cephalopods, however, dietary energy is rapidly mobilized from the digestive gland for growth rather than stored for reproduction. How excess energy is allocated for reproduction activity in cephalopods remains largely unclear. Lipogenesis is initiated by acetyl-CoA carboxylase (ACC), which converts acetyl-CoA derived from dietary carbon sources into malonyl-CoA; subsequent synthesis of saturated fatty acids is catalyzed by fatty acid synthase (FAS). Using the bigfin reef squid as a model, we investigate the role of fas in female development. fas mRNA was highly expressed in ovaries but weak in other tissues, including the lipid-rich digestive gland. fas showed female-biased expression in gonads, with level highest in juvenile ovaries and progressively decreasing to their lowest in mature ovaries. Expression was also high in primary and multiple follicular oocytes but declined in later stages. In situ hybridization and immunohistochemistry confirmed fas mRNA and protein localization in oocytes, particularly in primary and multiple follicular oocytes. In vitro ovarian culture further showed that inhibiting FAS activity enhanced somatic cell proliferation. Together, these findings suggest that squid ovary is a primary site of fatty acid synthesis, supporting early oocyte growth and membrane biogenesis in the absence of dedicated lipid storage tissues. The decline of FAS activity during oogenesis, and the associated reproduction in fatty acid synthesis, may act as a regulatory signal to promote somatic cell proliferation.

Mechanistic insights into capacitive ion exchange for selective divalent ion removal using activated carbon electrodes - Ming-Han Tsai; Shu-Ju Chao; David Chiuni Wang; I-Hsuan Lin; Li-Ching Chung; Po-I Liu; Lap-Cuong Hua; Hung-Yi Huang; Chi-Chang Hu (Chemical Engineering Journal, 2025)

Sequential slot-die coating of perovskite solar cell modules under ambient conditions with precise phase-transition control - Chia-Feng Li; Shih-Han Huang; You-Ren Chen; Hou-Chin Cha; Ssu-Yung Chung; Yu-Hung Hsiao; Feng-Yu Tsai; Yu-Ching Huang (Chemical Engineering Journal, 2025)

Singular value decomposition of near-field electromagnetic data for compressing and accelerating deep neural networks in the prediction of geometric parameters for through silicon via array - Song-En Chen; Eugene Su; Chih-Chung Wang; Jia-Han Li; Chao-Ching Ho (Computer Physics Communications, 2025)

Displacement evolution of failure and non-failure sliding rock slopes - Hsien-Li Kuo; Guan-Wei Lin; Ting-Yu Lin; Che-Hsin Liu; Chung-Ray Chu; Chih-Hsin Chang; Ching-Weei Lin; Hongey Chen (Landslides, 2025)

Large language models for diabetes training: a prospective study - Haoxuan Li; Zehua Jiang; Zhouyu Guan; Yuqian Bao; Yuexing Liu; Tingting Hu; Jiajia Li; Ruhan Liu; Liang Wu; Di Cheng; Hongwei Ji; Yong Wang; et al. (Science Bulletin, 2025)

Fire dynamics, fire generated pollutants, and acute health implications: A scaling law analysis of heavy-fuel-oil pool fires - Kuang-Chung Tsai; Li-Hsin Cheng; Chi-Fu Yeh; Tzu-Yan Tseng; Tzu-Ping Tseng; Li-Jen Huang; Shu-Hsing Yeh; Hui-Tsung Hsu; Ching-Ho Lin; Chin-Hsing Lai; Peter Brimblecombe; Ming-Jen Chen (Fuel, 2025)

Tidal currents and atmospheric inorganic nitrogen contribute to diurnal variation of dissolved nutrients and chlorophyll a concentrations in Mirs Bay, Hong Kong - Ho Wen Lo; Xu Yu; Hanzhe Chen; Wai Ching Chu; Nga Man Chung; Sze Wing Lau; Jinjian Li; Shumin Liang; Kezheng Liao; Henry Charles James Thomas; Ziyan Wang; Zijing Zhang; et al. (Regional Studies in Marine Science, 2025)

Regional sea level budget around Taiwan and Philippines over 2002‒2021 inferred from GRACE, altimetry, and in-situ hydrographic data - Wen-Hau Lan; Chi-Ming Lee; Chung-Yen Kuo; Li-Ching Lin; Eko Yuli Handoko (Journal of Geodesy, 2025)
The regional sea level budget and interannual sea level changes around Taiwan and Philippines are studied using altimetry, GRACE, and in-situ hydrographic data during 1993‒2021. Results show that the average sea level trend around Taiwan and Philippines during 1993–2021 derived from the altimetric data is 3.6 ± 0.2 mm/yr. Over 2002–2021, the study shows closure of sea level budget in the eastern ocean of Taiwan and Philippines within the observed data uncertainties, and the ocean mass accounts for 88%–100% of the observed sea level rise. In contrast, the sea level budget is not closed in the western ocean of Taiwan and Philippines, probably due to the lack of complete coverage by in-situ ocean observing systems. In addition, both regional sea level anomalies and their steric component around Taiwan and Philippines exhibit pronounced interannual and decadal variabilities. The trade wind stress associated with El Niño–Southern Oscillation and Pacific Decadal Oscillation offers a compelling explanation for the interannual and decadal signals of sea level anomalies in the southern ocean of Taiwan, with negative correlations of − 0.78 to − 0.64, indicating that trade wind stress makes a negative contribution to interannual-to-decadal sea level variability. In the northwestern ocean of Taiwan, the sea level variation is strongly influenced by the local monsoon system and shallow bathymetry with an annual amplitude of 90.3 ± 2.9 mm, larger than those in other regions around Taiwan and Philippines, where ocean mass is dominant with a high correlation with the sea level (+ 0.75 to + 0.78).

High efficiency in blue TADF OLED using favorable horizontal oriented host - Yi-Zhen Li; Hsuan-Chi Liang; Chia-Hsun Chen; Ching-Huang Chiu; Lian-Chun Huang; Yi-Ting Lee; Yi-Chung Dzeng; Chi Chen; Bo-Yen Lin; Jiun-Haw Lee; Tien-Lung Chiu; Man-kit Leung (Chemical Engineering Journal, 2024)

Protective effects of nordalbergin against LPS-induced endotoxemia through inhibiting MAPK/NF-κB signaling pathway, NLRP3 inflammasome activation, and ROS production - Pin-Rong Chen; Chia-Yang Li; Taha Yazal; I-Chen Chen; Po-Len Liu; Yi-Ting Chen; Ching-Chih Liu; Jung Lo; Tzu-Chieh Lin; Ching-Tang Chang; Hsin-En Wu; Yuan-Ru Chen; et al. (Inflammation Research, 2024)

The angiogenesis-modulating effects of coumarin-derivatives - Han-Ting Huang; Ching-Yuan Huang; Chih-Jou Lee; Bo-Jie Sun; Zong-Wei Jhang; Chi-Chung Wen; Yun-Hsin Wang; Tao-Sheng Li; Ching-Yuh Chern; Yau-Hung Chen (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Enhance electrocoagulation-flotation (ECF) removal efficiency perfluorohexanoic acid (PFHxA) by adding surfactants - Yueh-Feng Li; Chung-Yu Ho; Yu-Jung Liu; Yu-Chi Lee; Ching-Yao Hu; Shang-Lien Lo (Journal of Environmental Chemical Engineering, 2024)

Utilizing Numerical Models and GIS to Enhance Information Management for Oil Spill Emergency Response and Resource Allocation in the Taiwan Waters - Chi-Min Chiu; Laurence Zsu-Hsin Chuang; Wei-Liang Chuang; Li-Chung Wu; Ching-Jer Huang; Yinglong Joseph Zhang (Journal of Marine Science and Engineering, 2023)
This study aims to establish a comprehensive workflow for developing emergency response plans for both actual and scenario oil spill incidents in the Taiwan waters while addressing the resource allocation for oil spill containment as well. This workflow comprises two vital components. The first component involves the integration of numerical tools and observational data, which includes the incorporation of wind data from sources such as the National Centers for Environmental Prediction (NCEP) or meteorological stations. Additionally, it incorporates ocean current data simulated by the semi-implicit cross-scale hydroscience integrated system model (SCHISM) into the general NOAA operational modeling environment (GNOME) model, which is a new approach for this purpose. In order to assess the efficacy of this component, two distinct case studies were conducted. The first case study focused on an incident in a northern coastal area of Taiwan under open sea conditions, whereas the second case study examined an incident within a major commercial harbor in central Taiwan. The second component of this workflow involves creating oil risk maps by integrating the results from the first component with specific geographical factors into Google Earth. These oil risk maps serve multiple purposes. They offer real-time information to emergency response commanders regarding oil spill hazard prediction, and they also enable the effective development of emergency response strategies and disposal plans for potential oil spill incidents. This is achieved by generating risk maps for various scenarios using the approach outlined in the first component. Additionally, these maps assist in the assessment and planning of resource allocation for oil containment.

Duplicated paralog of sulfide: quinone oxidoreductase contributes to the adaptation to hydrogen sulfide-rich environment in the hydrothermal vent crab, Xenograpsus testudinatus - Chi Chen; Guan-Chung Wu; Yao-Tse Chung; Hau-Wen Li; Pei-Hsuan Chou; Yung-Che Tseng; Chieh-Jhen Chen; Sylvie Dufour; Ching-Fong Chang (Science of The Total Environment, 2023)

Corrigendum to: “Exposure to polystyrene microplastics impairs hippocampus-dependent learning and memory in mice” J. Hazard. Mater. 430 (2022) 128431 - Chiang-Wen Lee; Lee-Fen Hsu; I.-Lin Wu; Yung-Li Wang; Wei-Chen Chen; Yan-Jun Liu; Lu-Tang Yang; Chong-Lun Tan; Yueh-Hsia Luo; Chia-Ching Wang; Hui-Wen Chiu; Thomas Chung-Kuang Yang; et al. (Journal of Hazardous Materials, 2023)

Modelling chloroform in indoor swimming pool air and water: the influences of internal air circulation and occupants - Hui-Tsung Hsu; Ming-Jen Chen; Kuang-Chung Tsai; Li-Jen Huang; Ching-Ho Lin; Chin-Hsing Lai; Li-Hsin Cheng (Environmental Science and Pollution Research, 2023)

Transcriptomic profile of symbiotic accessory nidamental gland during female maturation in bigfin reef squid - Peng-Wei Tseng; Hau-Wen Li; Chih Chen; Yung-Che Tseng; Ching-Fong Chang; Guan-Chung Wu (Frontiers in Marine Science, 2023)
The bigfin reef squid, Sepioteuthis lessoniana , are a valuable commercial species in East Asian regions such as Taiwan and Japan. A lack of genomic information limits the application of potential aquaculture techniques, especially in breeding when considering the hatching rate of offspring. In some squids and cuttlefishes, symbiotic bacteria are transmitted from the accessory nidamental gland (ANG) to the jelly coat of eggs. In Hawaiian bobtail squid, these parent-delivered mutualistic bacteria play an important role in preventing lethal biofouling of the eggs and accelerating the hatch rate of offspring. The bacterial consortium, which is housed in the female squids ANG, are governed by host selection during female maturation. Immune functions are typically used to explain the regulatory mechanism of symbioses by host selection. In this study, we evaluated the transcripts featured in bacterial selection and maintenance during ANG development using RNA-seq. Different developmental stages of ANGs (stages 1–4) were sequenced. The de novo transcriptome assembly resulted in 524,918 unigenes. Two groups, non-pigmentation group (stage 1 and stage 3) and pigmentation group (stage 4), were clustered by transcriptome-wide expression profile analysis. The gene expression analyses indicated that 9,475 differential expression genes (DEGs) in three different phases and 1,363 (14.3%) DEGs were matched in the Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) databases. Furthermore, KEGG-enriched analysis results suggested that immune responses are a dominant pathway in the non-pigmentation group (stage 1 and stage 3) whereas lipid metabolism and metabolism of flora fermentation are dominant in the pigmentation group (stage 4). Although the host immunity plays an important role during bacterial colonization of the ANG in bigfin reef squid, our results showed that most immune-related genes had a reduced transcriptomic level in the pigmentation group compared with the non-pigmentation group. Therefore, our results provide new insight to understand the regulatory mechanisms of initial bacterial colonization and later bacterial pigmentation in the bigfin reef squid.

Streptococcus vulneris sp. nov., isolated from wound of patient with diabetic foot ulcer (DFU) - Jen-hao Chung; Li-Ting Wang; Yi-Sheng Chen; Yun-Shien Lee; Shih-Ting Lin; Yu-Chung Chang; Hui-Chung Wu; Yu-Jie Dai; Wei-Qi Liao; Fan-Ching Kao; Jui-hsiang Li (Archives of Microbiology, 2022)

The Characteristics and Expression Profile of Peptidoglycan Recognition Protein 2 in the Accessory Nidamental Gland of the Bigfin Reef Squid During Bacterial Colonization - Hau-Wen Li; Wei-Lun Kuo; Chi Chen; Yung-Che Tseng; Ching-Fong Chang; Guan-Chung Wu (Frontiers in Marine Science, 2022)
Some cephalopods carry microorganisms in two specialized organs, the light organ and the accessory nidamental gland (ANG). For the light organ, comprehensive mechanisms have been described for winnowing (bacterial selection) and maintenance of the symbiotic luminescent bacterium Vibrio fischeri ( V. fischeri ). However, the mechanisms controlling bacterial selection and maintenance during bacterial colonization of the ANG are open biological issues with physiological significance. Our recent study on bigfin reef squid ( Sepioteuthis lessoniana ) already showed that the ANG bacterial community shifts gradually and exhibits decreased diversity throughout maturation. This study further describes a potential role of an innate immunity-involved molecule, peptidoglycan recognition proteins (PGRPs), in the ANG of bigfin reef squid during bacterial transmission and colonization. First, we found that four homologs of the PGRP family are expressed in the ANG of bigfin reef squid ( sl PGRP2-5), but only slPgrp2 transcript levels are highly correlated with ANG development and bacterial colonization. Besides, slPgrp2 transcripts are mainly expressed in the epithelial cells of certain secondary tubules of ANG, and the expression levels are varied in the epithelial cells of other secondary tubules. This data reveals that slPgrp2 transcripts may associate with the composition of bacterial consortium and its secretary factors. Moreover, recombinant sl PGRP2 had a negative effect of Escherichia coli ( E.coli ) which inhibited bacterial growth in culture. Therefore, our data suggest slPgrp2 expression in the epithelial cells of secondary tubules in the ANG may have an essential role in the winnowing and maintenance of holobiont homeostasis in bigfin reef squid.

Identification of Neuronal Polarity by Node-Based Machine Learning - Chen-Zhi Su; Kuan-Ting Chou; Hsuan-Pei Huang; Chiau-Jou Li; Ching-Che Charng; Chung-Chuan Lo; Daw-Wei Wang (Neuroinformatics, 2021)
Identifying the direction of signal flows in neural networks is important for understanding the intricate information dynamics of a living brain. Using a dataset of 213 projection neurons distributed in more than 15 neuropils of a Drosophila brain, we develop a powerful machine learning algorithm: node-based polarity identifier of neurons (NPIN). The proposed model is trained only by information specific to nodes, the branch points on the skeleton, and includes both Soma Features (which contain spatial information from a given node to a soma) and Local Features (which contain morphological information of a given node). After including the spatial correlations between nodal polarities, our NPIN provided extremely high accuracy (>96.0%) for the classification of neuronal polarity, even for complex neurons with more than two dendrite/axon clusters. Finally, we further apply NPIN to classify the neuronal polarity of neurons in other species (Blowfly and Moth), which have much less neuronal data available. Our results demonstrate the potential of NPIN as a powerful tool to identify the neuronal polarity of insects and to map out the signal flows in the brain’s neural networks if more training data become available in the future.

Bioactive polyketides from the pathogenic fungus of Epicoccum sorghinum - Ching-Chia Chang; Chi-Ying Li; Yi-Hong Tsai; Mohamed El-Shazly; Chien-Kei Wei; Zih-Jie Yang; Shu-Li Chen; Chin-Chung Wu; Yang-Chang Wu; Fang-Rong Chang (Planta, 2021)

Targeting Inflammation, PHA-767491 Shows a Broad Spectrum in Protein Aggregation Diseases - Yu-Han Chung; Chia-Wei Lin; Hsin-Yu Huang; Shu-Ling Chen; Hei-Jen Huang; Ying-Chieh Sun; Guan-Chiun Lee; Guey-Jen Lee-Chen; Ya-Ching Chang; Hsiu Mei Hsieh-Li (Journal of Molecular Neuroscience, 2020)

Strictly Lobar Cerebral Microbleeds Are Associated with Increased White Matter Volume - Pei-Ning Wang; Kun-Hsien Chou; Li-Ning Peng; Li-Kuo Liu; Wei-Ju Lee; Liang-Kung Chen; Ching-Po Lin; Chih-Ping Chung (Translational Stroke Research, 2020)

High Circulatory Phosphate Level Is Associated with Cerebral Small-Vessel Diseases - Chih-Ping Chung; Li-Ning Peng; Kun-Hsien Chou; Li-Kuo Liu; Wei-Ju Lee; Ching-Po Lin; Liang-Kung Chen; Pei-Ning Wang (Translational Stroke Research, 2019)

Sensory determinants of valve rhythm dynamics provide in situ biodetection of copper in aquatic environments - Li-John Jou; Bo-Ching Chen; Wei-Yu Chen; Chung-Min Liao (Environmental Science and Pollution Research, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Diversity and functional characterization of bacterial endophytes dwelling in various rice (Oryza sativa L.) tissues, and their seed-borne dissemination into rhizosphere under gnotobiotic P-stress - Asif Hameed; Meng-Wei Yeh; Yu-Ting Hsieh; Wei-Ching Chung; Chaur-Tsuen Lo; Li-Sen Young (Plant and Soil, 2015)

A single-repeat MYB transcription repressor, MYBH, participates in regulation of leaf senescence in Arabidopsis - Chun-Kai Huang; Pei-Ching Lo; Li-Fen Huang; Shaw-Jye Wu; Ching-Hui Yeh; Chung-An Lu (Plant Molecular Biology, 2015)

BK Induces cPLA2 Expression via an Autocrine Loop Involving COX-2-Derived PGE2 in Rat Brain Astrocytes - Chih-Chung Lin; Hsi-Lung Hsieh; Shiau-Wen Liu; Hui-Ching Tseng; Li-Der Hsiao; Chuen-Mao Yang (Molecular Neurobiology, 2015)

Divergence of the expression and subcellular localization of CCR4-associated factor 1 (CAF1) deadenylase proteins in Oryza sativa - Wei-Lun Chou; Li-Fen Huang; Jhen-Cheng Fang; Ching-Hui Yeh; Chwan-Yang Hong; Shaw-Jye Wu; Chung-An Lu (Plant Molecular Biology, 2014)

Phylodynamics of H5N1 avian influenza virus in Indonesia - TOMMY TSAN‐YUK LAM; CHUNG‐CHAU HON; PHILIPPE LEMEY; OLIVER G. PYBUS; MANG SHI; HEIN MIN TUN; JUN LI; JINGWEI JIANG; EDWARD C. HOLMES; FREDERICK CHI‐CHING LEUNG (Molecular Ecology, 2012)
Understanding how pathogens invade and become established in novel host populations is central to the ecology and evolution of infectious disease. Influenza viruses provide unique opportunities to study these processes in nature because of their rapid evolution, extensive surveillance, large data sets and propensity to jump species boundaries. H5N1 highly pathogenic avian influenza virus (HPAIV) is a major animal pathogen and public health threat. The virus is of particular importance in Indonesia, causing severe outbreaks among poultry and sporadic human infections since 2003. However, little is known about how H5N1 HPAIV emerged and established in Indonesia. To address these questions, we analysed Indonesian H5N1 HPAIV gene sequences isolated during 2003–2007. We find that the virus originated from a single introduction into East Java between November 2002 and October 2003. This invasion was characterized by an initially rapid burst of viral genetic diversity followed by a steady rate of lineage replacement and the maintenance of genetic diversity. Several antigenic sites in the haemagglutinin gene were subject to positive selection during the early phase, suggesting that host‐immune‐driven selection played a role in host adaptation and expansion. Phylogeographic analyses show that after the initial invasion of H5N1, genetic variants moved both eastwards and westwards across Java, possibly involving long‐distance transportation by humans. The phylodynamics we uncover share similarities with other recently studied viral invasions, thereby shedding light on the ecological and evolutionary processes that determine disease emergence in a new geographical region.

Assessment of Radar Waveform Retracked Jason-2 Altimetry Sea Surface Heights Near Taiwan Coastal Ocean - Chung-Yen Kuo; Huan-Chin Kao; Hyongki Lee; Kai-Chien Cheng; Li-Ching Lin (Marine Geodesy, 2012)

Toxicokinetics/toxicodynamics with damage feedback improves risk assessment for tilapia and freshwater clam exposed to arsenic - Wei-Yu Chen; Chung-Min Liao; Yun-Ru Ju; Sher Singh; Li-John Jou; Bo-Ching Chen; Jeng-Wei Tsai (Ecotoxicology, 2012)

Polycyclic aromatic hydrocarbons in household dust near diesel transport routes - Chung-Yih Kuo; Heng-Chun Chen; Fang-Ching Cheng; Li-Ru Huang; Po-Shan Chien; Jing-Ya Wang (Environmental Geochemistry and Health, 2012)

Identification of QTL genes for BMD variation using both linkage and gene-based association approaches - Gloria Hoi-Yee Li; Ching-Lung Cheung; Su-Mei Xiao; Kam-Shing Lau; Yi Gao; Cora H. Bow; Qing-Yang Huang; Pak-Chung Sham; Annie Wai-Chee Kung (Human Genetics, 2011)

Association between human papillomavirus and adenocarcinoma of rectum and recto-sigmoid junction: a cohort study of 10,612 women in Taiwan - Li-Chung Chuang; Hui-Chi Chen; San-Lin You; Ching-Yu Lin; Mei-Hung Pan; Yi-Chun Chou; Chang-Yao Hsieh; Chien-Jen Chen (Cancer Causes & Control, 2010)

A Mediated Glucose Biosensor Incorporated with Reverse Iontophoresis Function for Noninvasive Glucose Monitoring - Congo Tak-Shing Ching; Tai-Ping Sun; Su-Hua Huang; Hsiu-Li Shieh; Chung-Yuan Chen (Annals of Biomedical Engineering, 2010)

Expression and localization of Tmie in adult rat cochlea - Mao-Chang Su; Jiann-Jou Yang; Ming-Yung Chou; Chung-Han Hsin; Ching-Chyuan Su; Shuan-Yow Li (Histochemistry and Cell Biology, 2008)

The blood-brain barrier in the cerebrum is the initial site for the Japanese encephalitis virus entering the central nervous system - Tsan-Hsiun Liu; Li-Ching Liang; Chien-Chih Wang; Huei-Chung Liu; Wei-June Chen (Journal of NeuroVirology, 2008)

A rice phenomics study—phenotype scoring and seed propagation of a T-DNA insertion-induced rice mutant population - Chyr-Guan Chern; Ming-Jen Fan; Su-May Yu; Ai-Ling Hour; Po-Chang Lu; Yao-Cheng Lin; Fu-Jin Wei; Sheng-Chung Huang; Shu Chen; Ming-Hsing Lai; Ching-Shan Tseng; Hsing-Mu Yen; et al. (Plant Molecular Biology, 2007)

A rice gene activation/knockout mutant resource for high throughput functional genomics - Yue-Ie Hsing; Chyr-Guan Chern; Ming-Jen Fan; Po-Chang Lu; Ku-Ting Chen; Shuen-Fang Lo; Peng-Kai Sun; Shin-Lon Ho; Kuo-Wei Lee; Yi-Chieh Wang; Wen-Lii Huang; Swee-Suak Ko; et al. (Plant Molecular Biology, 2007)

Cloning and characterization of a DEAD box RNA helicase from the viable seedlings of aged mung bean - Sing-Chung Li; Mei-Chu Chung; Ching-San Chen (Plant Molecular Biology, 2001)